2014
DOI: 10.1080/09500693.2013.879622
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Changes in Science Teaching Orientations and Technology-Enhanced Tools for Student Learning in the Context of Professional Development

Abstract: This research examines how science teaching orientations and beliefs about technology-enhanced tools change over time in professional development (PD). The primary data sources for this study came from learning journals of 8 eighth grade science teachers at the beginning and conclusion of a year of PD. Based on the analysis completed, Information Transmission (IT) and Struggling with Standards-Based Reform (SSBR) profiles were found at the beginning of the PD, while SSBR and Standards-Based Reform (SBR) profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…As in other studies (Campbell et al, 2014;Walker et al, 2012), teachers in the present investigation indicated after the professional development that they grew professionally in understanding how to provide differentiated instruction to students and in integrating technology into their instruction. These topics are critical for teaching strategies for online academic research, and the results show that the face-to-face professional development provided reasonable coverage with relevant discussions and high-quality materials focused on differentiated instruction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As in other studies (Campbell et al, 2014;Walker et al, 2012), teachers in the present investigation indicated after the professional development that they grew professionally in understanding how to provide differentiated instruction to students and in integrating technology into their instruction. These topics are critical for teaching strategies for online academic research, and the results show that the face-to-face professional development provided reasonable coverage with relevant discussions and high-quality materials focused on differentiated instruction.…”
Section: Discussionsupporting
confidence: 75%
“…Professional development that incorporates technology integration has been shown to result in more positive and sophisticated beliefs among teachers about using technology in their teaching (Campbell, Zuwallack, Longhurst, Shelton, & Wolf, 2014). Ritzhaupt, Dawson, and Cavanaugh (2012) found that students made better use of technology for learning when it was integrated effectively by their teachers into the curriculum, which could be enhanced by teachers' prior technology experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…I didn't really do inquiry before… and now I do it often. I had always been taught that inquiry was the thing I should be striving for, but I had never seen it in action or had anyone explain to me how to implement it (Campbell et al 2014(Campbell et al , p. 1840.…”
Section: Reformed-based and Technology-integrated Instructionmentioning
confidence: 99%
“…• Students can also see in real time how charts and graphs change as data are put into a data table. • It [technology-Google Docs specifically] is also a way for them to organize data that they collect in other class investigations and a way to communicate or collaborate with their work groups or with me [the teacher] (Campbell et al 2014(Campbell et al , p. 1835 Koehler and Mishra (2005), as well as other researchers (e.g., Campbell and Abd-Hamid 2013;Crippen 2012;Niess 2005;Pamuk 2012), have identified how TPACK takes into account another realm of teacher knowledge (i.e., technology) and considers the role TPACK plays in teachers' conceptualization and enactment of instruction in classrooms. While more research is certainly needed to learn more about the decisions teachers in this study are making about using technological resources in science instruction, these findings, especially significant improvements in TUSI ratings recorded through classroom observations when comparing before and after 1 year of PD, provide initial evidence of teachers' developing TPACK for reformed-based science teaching that moves beyond the more commonly found traditional applications of technology in science classrooms described by Bell et al (2013), , and .…”
Section: Reformed-based and Technology-integrated Instructionmentioning
confidence: 99%
See 1 more Smart Citation